Exoproteomic profiling uncovers critical determinants for virulence of livestock-associated and human-originated Staphylococcus aureus ST398 strains. Issue 1 (1st January 2020) - Zhao, Xin; Chlebowicz-Flissikowska, Monika A.; Wang, Min; Vera Murguia, Elias; de Jong, Anne; Becher, Dörte; Maaß, Sandra; Buist, Girbe; van Dijl, Jan Maarten
ABSTRACT: Staphylococcus aureus: with the sequence type (ST) 398 was previously associated with livestock carriage. However, in recent years livestock-independent S. aureus ST398 has emerged, representing a potential health risk for humans especially in nosocomial settings. Judged by whole-genome sequencing analyses, the livestock- and human originated strains belong to two different S. aureus ST398 clades but, to date, it was not known to what extent these clades differ in terms of actual virulence. Therefore, the objective of this study was to profile the exoproteomes of 30 representative S. aureus ST398 strains by mass spectrometry, to assess clade-specific differences in virulence factor secretion, and to correlate the identified proteins and their relative abundance to the strains' actual virulence. Although the human-originated strains are more heterogeneous at the genome level, our observations show that they are more homogeneous in terms of virulence factor production than the livestock-associated strains. To assess differences in virulence, infection models based on larvae of the wax moth Galleria mellonella and the human HeLa cell line were applied. Correlation of the exoproteome data to larval killing and toxicity toward HeLa cells uncovered critical roles of the staphylococcal Sbi, SpA, SCIN and CHIPS proteins in virulence. These findings were validated by showing that sbi or spa mutant bacteria are attenuated in G. mellonella and that the purified SCIN and CHIPS proteins are toxic for HeLa cells. Altogether, we show that exoproteome profiling allows the identification of critical determinants for virulence of livestock-associated and human-originated S. aureus ST398 strains.